Role of maternal tryptophan metabolism in allergic diseases in the offspring. Issue 10 (24th June 2021) - Lau, Hui Xing; El‐Heis, Sarah; Yap, Qai Ven; Chan, Yiong Huak; Tan, Cheryl Pei Ting; Karnani, Neerja; Tan, Karen Mei Ling; Tham, Elizabeth Huiwen; Goh, Anne Eng Neo; Teoh, Oon Hoe; Tan, Kok Hian; Eriksson, Johan Gunnar; et al.
Abstract: Background: Nicotinamide (vitamin B3) is a metabolite of tryptophan and dietary precursor of enzymes involved in many regulatory processes, which may influence fetal immune development. Objective: We examined whether maternal plasma concentrations of nicotinamide, tryptophan or nine related tryptophan metabolites during pregnancy were associated with the risk of development of infant eczema, wheeze, rhinitis or allergic sensitization. Methods: In the Growing Up in Singapore Towards Healthy Outcomes (GUSTO) study, we analysed the associations between maternal plasma levels of nicotinamide, tryptophan and tryptophan metabolites at 26–28 weeks of gestation and allergic outcomes collected through interviewer‐administered questionnaires at multiple time‐points and skin prick testing to egg, milk, peanut and mites at age 18 months. Multivariate analysis was undertaken adjusting for all metabolites measured and separately adjusting for relevant demographic and environmental exposures. Analyses were also adjusted for multiple comparisons using the false discovery method. Results: Tryptophan metabolites were evaluated in 976/1247 (78%) women enrolled in GUSTO. In multivariate analysis including all metabolites, maternal plasma 3‐hydrokynurenine was associated with increased allergic sensitization at 18 months (AdjRR 2.6, 95% CI 1.3–5.2 for highest quartile) but the association with nicotinamide was not significant (AdjRR 1.8, 95% CI 0.9–3.6). In analysis adjusting for other exposures, both 3‐hydrokynurenine and nicotinamide were associated with increased allergic sensitization (AdjRR 2.0, 95% CI 1.1–3.6 for both metabolites). High maternal plasma nicotinamide was associated with increased infant eczema diagnosis by 6 and 12 months, which was not significant when adjusting for all metabolites measured, but was significant when adjusting for relevant environmental and demographic exposures. Other metabolites measured were not associated with allergic sensitization or eczema, and maternal tryptophan metabolites were not associated with offspring rhinitis and wheeze. Conclusions and Clinical Relevance: Maternal tryptophan metabolism during pregnancy may influence the development of allergic sensitization and eczema in infants. Abstract : Maternal tryptophan metabolism during pregnancy may influence the development of allergic sensitization and eczema in infants.